Effect of supercritical carbon dioxide treatment on structure and mechanical properties of β-nucleated polypropylene processed at different temperatures. (July 2017) - Geng, Chengzhen; Bai, Hongwei; Fu, Qiang; Luo, Feng
Abstract: Polypropylene (PP) was compounded with β-nucleating agent and injection-molded at 180 °C or 220 °C. The samples were subsequently treated by supercritical carbon dioxide (scCO2 ) at different temperatures. Results show that processing temperature and scCO2 treatment could strongly influence the tensile and impact properties of β-nucleated PP. In particular, the sample processed at 220 °C and treated at 120 °C exhibit much enhanced impact strength (4.8 times that of its untreated counterpart). FTIR, WAXD, SEM and DMA were performed to explore the effects of processing temperature and scCO2 treatment on structure of the samples. Deformation-induced plastic flow and micro-voids were also evaluated to construct structure-property relations. It was found that the influence of processing temperature on mechanical properties is mainly associated with the β-form content and β-crystalline morphology, while the structural changes in the crystalline lamellar scale may be responsible for the toughening effect of scCO2 treatment.